Knowledge transfer in non-profit organisations: a qualitative study. (23rd April 2019) - Barpanda, Saswat; Thamatoor, Mridula
In this 21st century, the importance of knowledge transfer is evident in all the organisation. There are two reasons. First, knowledge appears to be an increasing proportion of the total asset. Second, the advance in information technology has created new means of knowledge transfer. Effective knowledge transfer can improve the organisation performance and gain competitive advantage. There is only a limited research done on the knowledge transfer in non-profit organisations. This paper tries to highlight the relevance of knowledge transfer and the factors contributing to it in non-profit organisations and how it shapes various organisational processes. A qualitative study has been used in this research considering 4 non-governmental organisations in the Southern state of Kerala, India. The primary data has been collected through unstructured interview and the secondary data from the reports, newsletters, articles, organisational, and websites. Content analysis and other exploratory methods using Nvivo software have been used to analyse the data. The outcome of the study would be to provide a framework that intends to help the non-profit organisations to plan, conduct and evaluate the efforts which are used to transfer knowledge with others.